1998
DOI: 10.1088/0954-3899/24/11/007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spin oscillation of relativistic particles passing through substance and the possibility of constituent quark rescattering observation at -hyperon-proton collision

Abstract: For the Ω --hyperon passing through matter the phenomena of spin rotation and oscillation has investigated quantitatively. Connection of these phenomena with constituent quark rescattering has been determined. It allows one to investigate quark rescattering directly without background of a single scattering.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…This property unites the quasioptical phenomena discovered in [1][2][3][4][5][6][7][8] for interaction of spin-particles in matter with nuclei with the phenomena existing in light optics. However, attention should be drawn to the fact that whereas the photon spin is equal to unity, the particle (atom, nucleus) spin may take on different values.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…This property unites the quasioptical phenomena discovered in [1][2][3][4][5][6][7][8] for interaction of spin-particles in matter with nuclei with the phenomena existing in light optics. However, attention should be drawn to the fact that whereas the photon spin is equal to unity, the particle (atom, nucleus) spin may take on different values.…”
supporting
confidence: 52%
“…In [1][2][3][4][5][6][7][8] a wide range of phenom-ena similar to the effects of light polarization plane rotation and birefringence was shown to exist for particles other than photons. In particular it has been shown that as particles (neutrons, protons, neutrinos, etc.)…”
mentioning
confidence: 99%
“…For the particles with spin S _> 1 the spin oscillation and rotation exist even in unpolarized targets and its value does not decrease with particle energy grows [1,2,3] at high energies.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis by the frame of the Glauber multiscattering theory [2,3] shows that T2 is determined by rescattering of colliding particle constituents only i.e. the first term of Glauber series (single scattering) does not contribute to T2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation